Global geotourism perspectives - Dowling, Ross Kingston; Newsome, David, 1951- (Goodfellow Publishers, 2010)
Annotation With contributions from a team of international researchers, specialists, practitioners, and protected area managers, this volume illustrates how geotourism is developing in countries within six continents and countries including Australia, Brazil, China, Greece, Ireland, Japan, Malaysia, Mauritius, Oman, South Africa, and the USA.